POLA ASUH ORANG TUA SEBAGAI TUKANG PANGKAS RAMBUT TERHADAP ANAK DI KECAMATAN TAMPAN KOTA PEKANBARU - Achmad, Said Suhil Achmad Suhil; Maemunaty, Titi Maemunaty Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the parenting of barbershop at Tampan village, Pekanbaru city. Formulation of the problem in this research is how high the level of parentinand what parentings model the highest used by barber? This is a descriptive study with a quantitative approach which aims to describe the result with figures. The sampling technique using a quota sampling technique, with the theoretical basis according Sugiyono. Data collection techniques in this study is by using a questionnaire, which was 60 statement item. The data obtained from respondents who were 30 to sample the test and 33 for the study. After polling in the trial, there are one items that are not valid, and the researchers not removed the item according Chu Yan Piaw opinion, so the whole instrument reliably indicated by Cronbach alpha = 0.97. The result of the data analysis shows that the parenting of barbers of permisivve indicator is high with the value of mean 4.43 and Standard Deviation (SD) 0.69, compared with democratic parenting and authoritarian. So upbringing according to some barber deemed useful, moreover, in order to cultivate the childâs confidence.Keywords : Parenting, Barbershop